Basic Concepts of a Phase-Locked Loop Control System - Sefraoui, Hanane; Salmi, Khalid; Ziyyat, Abdelhak (International Journal of Online and Biomedical Engineering (iJOE), 2022)
Phase-locked loop (PLL) is one of the main components of modern electronic design and has been around for a considerable number of years. It is a technique that has greatly contributed to the technological advancement of communications and control systems. This paper presents a phase-locked loop tutorial based on a control system, it gives a concise review of basic concepts, the different types of PLLs, linear analysis approaches of analog systems PLL is discussed, furthermore the theoretical analysis of the steady-state error in detail is presented, and its simulations of different phase offset values in C program are presented, and show how the response of the loop changes.